Gambaran Persepsi Masyarakat dalam Penanganan Limbah Masker pada Masa Pandemi Covid-19 di DKI Jakarta - Awaluddin Hidayat Ramli Inaku; Cornelis Novianus; Bety Semara Lakhsmi (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
Background: The problem of waste is not a new problem in Indonesia. The government has submitted the obligation to use masks since early 2002. The volume of waste that continues to increase in line with the increasing cases of Covid-19 in DKI Jakarta affects the production of mask waste. Objectives: This study aims to describe the public perception of handling mask waste during the Covid-19 pandemic. in DKI Jakarta. Methods: This type of research is a qualitative research with an analytical survey method. The instrument used is a questionnaire, the population is all residents in DKI Jakarta and the sample is 406 respondents. The data analysis used is descriptive analysis to get a general picture of the public's perception of the management of mask waste. Results: Based on the results of the study, it was found that there were positive and negative results from each question item regarding the management of mask waste as follows, 85.07% of the community had a positive perception of mask waste, 100% positive for sorting, collecting, transporting and treating mask waste. Conclusion: from these results it was concluded that the public had an understanding of how to manage medical waste during the Covid-19 pandemic.